Kesehatan Reproduksi dan Budaya Patriarki dalam Novel Bulan Patah Karya Maria Maltidis Banda - Ariasih, Ni Putu Ayu; S. Pidada, Ida Bagus Jelantik; Kusuma, I Nyoman Weda (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 2 (2023): Volume 2 No 2, April 2023, 2023)
This research is entitled "Reproductive Health and Patriarchal Culture in the Novel Bulan Patah by Maria Maltidis Banda".  The purpose of this study was to determine the structural elements which include grooves;  characterizations;  and setting, to reveal aspects of reproductive health in a patriarchal culture in the novel Bulan Patah by Maria Matildis Banda, and to reveal the meaning of filial piety in the novel Bulan Patah. The theory used in this research is the theory of structure and the theory of sociology of literature which includes reproductive health and public health. This study uses qualitative data.  The data collection method used is the literature study method.  The process of data analysis used the descriptive qualitative method. The data sources of this research are primary data and secondary data. The results of this study, namely the plot in the novel Bulan Patah are divided into three stages, namely the initial, middle, and final stages.  The main character in this novel is Midwife Rosa Dalima, while the secondary character is Om Saver.  The complementary characters in this novel are Rachel and Retha.  The setting in this novel is the setting of the place, setting of time, and setting of atmosphere.  In this study, it was found that the aspects of reproductive health were weak without the treatment of a doctor or midwife, and weak physical and social conditions, due to the influence of patriarchal culture in Bulan Patah Novel.  In addition, this study also found that the role of Midwife Rosa Dalima in the novel Bulan Patah was related to the meaning of filial piety for health development.